Merchant Credit and the Informal Economy : Newfoundland, 1919-1929 - Ommer, Rosemary (Historical Papers / Communications historiques, 1989)
AbstractMerchant credit systems and household production have usually been examined historically as two distinct entities which either bore no relationship to one another or else operated in opposition. This paper proposes instead that there has existed a somewhat unequal symbiosis between these two economic systems, not only in the early of settlement when labour was scarce, but also under conditions of abundant labour. It further suggests that merchant credit can fruitfully be regarded as the forerunner of state welfare systems insofar as both have provided the start-up capital for informal economies which, in their turn, then operate as an essential safety net for people living in marginal economies.